2014
DOI: 10.1007/s13595-013-0347-z
|View full text |Cite
|
Sign up to set email alerts
|

Back to the roots: how do seedlings of native tree species react to the competition by exotic species?

Abstract: to the roots: how do seedlings of native tree species react to the competition by exotic species?.Abstract & Context Identifying the traits of exotic species may explain their invasiveness and help control the negative impacts of these species on native ecosystems. In this study, we investigated root competition as an important driver for the competitiveness of two exotic tree species in the seedling stage. & Aims In a pot experiment, carried out in Central Europe, we studied the effect of root competition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
(46 reference statements)
2
22
2
Order By: Relevance
“…Similar results were also reported by Jose et al (2003). By contrast, there were no significant changes in the biomass allocation of R. pseudoacacia between above-and belowground organs, suggesting its strong competitiveness or increased resource acquisition efficiency (Kawaletz et al 2013a). Although Q. acutissima adopted this strategy, it still could not offset the strong competition from R. pseudoacacia.…”
Section: Functional Traits Under Competitionsupporting
confidence: 83%
“…Similar results were also reported by Jose et al (2003). By contrast, there were no significant changes in the biomass allocation of R. pseudoacacia between above-and belowground organs, suggesting its strong competitiveness or increased resource acquisition efficiency (Kawaletz et al 2013a). Although Q. acutissima adopted this strategy, it still could not offset the strong competition from R. pseudoacacia.…”
Section: Functional Traits Under Competitionsupporting
confidence: 83%
“…Some of these studies indicated a lack of differences in rmf (Grotkopp et al 2010; Matzek 2011) while some showed higher rmf (Kuehne et al 2014) and some lower rmf (Paquette et al 2012;González-Muñoz et al 2014) of alien species. Biomass allocation to the root systems also depends on root competition (Kawaletz et al 2014). Investment in acquisitive traits causes a competitive advantage over native species (Blossey and Notzold 1995;te Beest et al 2015).…”
Section: Trait Valuesmentioning
confidence: 99%
“…Young regeneration is especially vulnerable to limiting abiotic factors, for instance frost or drought (Niinemets and Valladares 2006;Eckstein et al 2011;Jagodziński et al 2017), as well as to herbivory (de Chantal and Granström 2007;Iszkuło et al 2014;Bodziarczyk et al 2017), leading to low survival rates. Another important factor is competition with understory herbaceous species (Lorimer et al 1994;Emborg 1998;Chmura and Sierka 2007), as well as competition within the regeneration layer, both intra-and interspecific (Janzen 1970;Robakowski and Bielinis 2011;Kawaletz et al 2014;Martínez-García et al 2015). For that reason, assessment of natural regeneration is crucial both for understanding dynamics of forest species composition and for developing forest management strategies.…”
Section: Introductionmentioning
confidence: 99%